FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN - BAHRI, SYAIFUL (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2017)
The purpose of this study is to examine the effect of good corporate governance, profitability, liquidity, free cash flow, firm size, leverage, collateral assets, and institutional ownership of dividend policy. The research population of manufacturing companies listed on the Indonesia Stock Exchange in 2013 until 2015. The sample of research by using purposive sampling of the research sample selection of 47 manufacturing companies within 3 years and with the number of units of analysis as much as 141. The results show that good corporate governance, liquidity, free cash flow, leverage, collateral assets, and institutional ownership have no effect on dividend policy. Profitability and firm size affect the dividend policy effect on dividend policy.